TEOREMA TITIK TETAP BANACH PADA RUANG METRIK-D - Muhammad Ahsar Karim; Dewi Sri Susanti; Nurul Huda (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2010)
In the space of metrics known the fixed point theorem of Banach. In this paper, the theorem will be constructed in the D-metric space. This study begins with construction concepts: open ball, open set, convergent lines, and Cauchy rows respectively in the D-metric space. Then given the concept of continuous mapping and mapping continuous uniform in the D-metric space. Further constructed Banach's fixed point theorem at in the D-metric space.